Public procurement and the EU competition rules - Sánchez Graells, Albert (Hart Pub., 2011)
"Public procurement and competition law are both important fields of EU law and policy, intimately intertwined in the creation of the internal market. Hitherto their close connection has been noted, but not closely examined. This new work is the most comprehensive attempt to date to explain the many ways in which these fields, often considered independent of one another, interact and overlap in the creation of the internal market. In this process of convergence between competition and public procurement law, the need for this joint study is clearly apparent. As such the book asks whether competition law principles inform or condition public procurement rules, and whether they are adequate to ensure that competition is not distorted in markets where public procurement is particularly significant. The book moves away from the classical focus of public procurement on the activities of private actors, developing instead an analytical framework for the appraisal of the market behaviour of the public buyer from a competition perspective. The analysis is both legal and economic. Proceeding through a careful assessment of the general rules of competition and public procurement, the book constantly tests the efficacy of the rules in competition and public procurement against a standard of the proper functioning of undistorted competition in the market for public procurement"--Provided by publisher